Hubungan Edukasi Melalui Media Leaflet Terhadap Tingkat Pengetahuan Ibu Tentang Penggunaan Rebusan Jahe Dan Madu Pada Balita Penderita ISPA Di Desa Nyalindung Wilayah Kerja Puskesmas Cijedil Tahun 2023 - Neng Sumyati; Siti Kamillah; Rina Afrina (Pusat riset dan Inovasi Nasional, 2024)
Acute Respiratory Infection (ARI) is a health problem that often occurs in toddlers. Health education through leaflet media is an effort to convey health messages and is an important strategy in increasing mothers' knowledge and awareness of the use of herbal remedies including ginger and honey decoction for toddlers. This research aims to determine the relationship between education through leaflet media and the level of knowledge of mothers regarding the use of ginger and honey decoction in toddlers suffering from ISPA in Nyalindung Village, Cijedil Health Center Working Area in 2023. The method used is pre-experimental, one-group pretest-posttest design without there is a control group where data collection and variable measurement are carried out at the same time. The sample in this study was 83 respondents. The results of the study showed a significant increase in mothers' knowledge before being given the intervention and after being given the intervention. The average score before being given education was 8.10 and the average score after being given the intervention was 12.33, meaning there was an increase of 4.23. The Wilcoxon test obtained a p-value of 0.000 < 0.05, which means Ha was accepted. This result shows that education through leaflet media is effective in increasing mothers' knowledge about the use of ginger and honey decoction for toddlers. The advice from this research is that it is hoped that mothers will continue to explore information by continuing to participate in outreach activities or with other media such as electronic media by understanding the information presented and being able to apply herbal medicine correctly and safely.